Про повноту та єдиність універсального каркаса в реляційній моделі даних - Panchenko, B. E.; Pysanko, I. M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
Ideas about routes for normalization in the universal framework of relational databases and their topology are introduced. A theorem about the completeness and uniqueness of the relational framework is formulated and proved.